1999
DOI: 10.1159/000007995
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide Vasoreactivity in Vascular Dementia: A Positron Emission Tomographic Study

Abstract: The present study investigates the vasoreactivity of the brain in patients with large infarcts and dementia (multi-infarct dementia; MID) and in patients with microangiopathy, lacunes, white matter changes and dementia (lacunar dementia; LD) using positron emission tomography (PET) and 13NH3 as regional cerebral blood flow (rCBF) tracer. In the control group, an increase in rCBF ranging from 32 to 43% was found in all brain regions after intravenous acetazolamide administration. In both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…For example, Nagata et al 5 measured MTT and VR to carbon dioxide inhalation in patients with AD and VD and found that MTT was prolonged and VR was depressed in patients with VD, whereas the 2 indices were preserved in patients with AD. 5 Impairment in the responsiveness to vascular activation in VD was reported by De Reuck et al, 15 whereas other groups found no such impairment in AD based on SPECT [16][17][18] and xenon-enhanced CT 19 analysis. Moreover, Puls et al 20 revealed, by using transcranial sonography, that tissue transit time is prolonged in VD but not in degenerative dementia.…”
Section: Discussionmentioning
confidence: 86%
“…For example, Nagata et al 5 measured MTT and VR to carbon dioxide inhalation in patients with AD and VD and found that MTT was prolonged and VR was depressed in patients with VD, whereas the 2 indices were preserved in patients with AD. 5 Impairment in the responsiveness to vascular activation in VD was reported by De Reuck et al, 15 whereas other groups found no such impairment in AD based on SPECT [16][17][18] and xenon-enhanced CT 19 analysis. Moreover, Puls et al 20 revealed, by using transcranial sonography, that tissue transit time is prolonged in VD but not in degenerative dementia.…”
Section: Discussionmentioning
confidence: 86%
“…Hand-searching identified 3 additional publications. Of the 30 for full text reading, 3 were excluded (unable to translate: Russian 16 and Slovakian 17,18 ) and 11 failed to meet the inclusion criteria (no control subjects, 19,20 not assessing dynamic endothelial function, or inappropriate patients [21][22][23][24][25][26][27][28][29] ). Therefore, 16 papers were eligible, including 974 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Lacunar strokes were defined by criteria of classic lacunar syndromes, with or without radiological deep lesions no more than 1 cm in diameter. 7 Cardioembolic strokes were defined by a combination of clinical and echocardiographic criteria. Ischemic strokes without a lacunar or cardioembolic origin were classified as large-artery strokes.…”
Section: See Editorial Comment Page 1916mentioning
confidence: 99%
“…The mechanism is not considered to be chronic low perfusion as cerebral blood flow in affected areas lies within normal limits at rest or is modestly decreased in proportion to tissue loss. There is, however, clear evidence of diminished perfusion reserve, 6,7 and it is hypothesized that episodic mild ischemia occurs as a result of intermittent changes in cerebral perfusion pressure. The process has been termed "incomplete infarction."…”
Section: Editorial Comment the Progression Of Leukoaraiosismentioning
confidence: 99%